Estilos de liderança e desempenho das equipes no setor público - Maria Aparecida Muniz Jorge (2014)
This research aims to analyze how leadership styles of public managers influence the performance of the direct administration, independent and foundation management teams in the Executive Power in the State of Minas Gerais. From the Bass and Avoio (2000) model - which establishes three leadership styles - transactional, transformational and laissez-faire and Fernandes (2013) model, related to the performance - outputs expressed in terms of deliveries and results - the existing leadership styles were identified in the agencies and entities of the Executive Power in Minas Gerais and it was made a influence analysis of the team performance levels. The importance of researching the leadership themes and team performance in the public sector comes from the transformation context that it has experienced. From the New Public Management movement, started in Brazil during the 1990s, and in Minas Gerais in 2013, with the Choque de Gestão (Shock Management) implementation. The public organizations are increasingly charged for achieve results and, therefore, an effective leadership are necessary to be able to mobilize their teams towards to the objectives and goals established. A quantitative survey was conducted, through the application of a questionnaire to a sample of 82 leaders and 233 subordinates, who answered questions related to leadership styles and the team performance concerning the deliveries made. Secondary data were also used to measure the teams performance regarding the results, represented by the note of the 2° stage Results Agreement (agreed targets instrument with teams, existing in the agencies and entities in the Executive Power of State). Based on the data analysis, it was verified that the transformational and transactional leadership styles positively affects the team performance and the laissez-faire leadership style does not significantly influence team performance, regarding to deliveries variable. Contrary to the literature signaled, it was identified that the transactional leadership style affects more positively the teams deliveries compared to transformational leadership style. Another result that deserves mention concerns the fact that leadership style did not significantly explain the teams performance regarding to the note of the Results Agreement, despite all the logic to manage for results that have been implemented in the Executive Power of the State. When separated the results by leaders group and subordinates, it was identified a difference perception between them regarding leadership styles that influence the deliveries of each team. In this aspect, the leaders consider the transformational leadership style creates a higher level of deliveries, converging with that theory proclaims about leadership styles, while the subordinates understand that transactional leadership is the one that obtains a higher level of deliveries. Therefore, it is believed that the proposed objectives of this research were fulfilled and it could contribute to a better understanding of leadership styles and their influences on the team performance of the agencies and entities in the Executive Power of the State. Futhermore, the results creates subsidies for development policies design and leardeship formation.